Effects of the morphology of sulfobetaine zwitterionic layers grafted onto a silicone surface on improving the hydrophilic stability, anti‐bacterial adhesion properties, and biocompatibility. Issue 44 (31st August 2018) - Cao, Qin; Wu, Shuqing; Wang, Liying; Shi, Xuetao; Li, Guangji
ABSTRACT: Though silicone rubber has been used in the biomedical field, its inherent hydrophobic nature and "hydrophobic recovery" limit its wide application. In this article, cross‐linked and comb‐like sulfobetaine zwitterionic layers were covalently grafted onto the surface of a silicone film (SF) by ultraviolet (UV) curing in the presence and absence of cross‐linking agent, respectively, after the surface was pretreated under high‐energy vacuum ultraviolet (VUV) irradiation. Comparative studies were carried out to investigate the effects of the grafting layers on the surface properties, hydrophilic stability, anti‐bacterial adhesion property, and cytocompatibility. The results showed that VUV‐UV irradiation is an efficient modification method for introducing hydrophilic groups onto SF surface. The covalently linked zwitterions endowed the silicone surface with good hydrophilicity, a better reduction in the adhesion of bacteria relative to the properties of a pristine silicone surface. The cross‐linked layer exhibited better hydrophilic stability, anti‐bacterial adhesion properties and biocompatibility due to better coverage of the surface than the comb‐like layer. The improvement in these properties provides the potential for the extensive application of modified silicone films in silastic implants and medical dressings. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46860. Abstract :